Relic photon temperature versus redshift and the cosmic neutrino background - Hofmann, Ralf (Annalen der Physik, 2015)
Presuming that CMB photons are described by the deconfining phase of an SU(2) Yang-Mills theory with the critical temperature for the deconfining-preconfining phase transition matching the present CMB temperature K (SU(2)CMB), we investigate how CMB temperature T connects with the cosmological scale factor a in a Friedmann-Lemaître-Robertson-Walker Universe. Owing to a violation of conformal scaling at late times, the tension between the (instantaneous) redshift of reionisation from CMB observation () and quasar spectra () is repealed. Also, we find that the redshift of CMB decoupling moves from to which questions ΛCDM cosmology at high redshifts. Adapting this model to the conventional physics of three flavours of massless cosmic neutrinos, we demonstrate inconsistency with the value Neff ∼ 3.36 extracted from Planck data. Interactions between cosmic neutrinos and the CMB implies a common temperature T of (no longer separately conserved) CMB and neutrino fluids. Neff ∼ 3.36 then entails a universal, temperature induced cosmic neutrino mass with . Our above results on zre and zdec, derived from SU(2)CMB alone, are essentially unaffected when including such a neutrino sector.
Gesehen am 07.09.2020